Information technology. International standardized profile RA. Relaying the connectionless-mode network service. Definition of profile RA51.54, relaying the connectionless-mode network service between CSMA/CD LAN subnetwork and FDDI LAN subnetworks Part 6, (15th July 1995) - British Standards Institution,
No abstract available